Achievement Goal Orientations and Self-Reported Study Strategies as Predictors of Online Studying Activities. (December 2015) - Adesope, Olusola O.; Zhou, Mingming; Nesbit, John C.
The purpose of this study was to investigate whether achievement motivations influence the adoption of learning strategies and learning strategies influence studying behavior in an online learning environment. The Goal Orientation Questionnaire was used to measure achievement motives, and the Motivated Strategies for Learning Questionnaire was used to assess learning strategies. In addition, data on how learners tagged and annotated the learning materials were collected using software designed to aid studying and to examine studying behavior. Confirmatory factor analyses were conducted on Goal Orientation Questionnaire data from 170 university students who used the learning software to study a chapter from a textbook. Results showed that task value and effort regulation subscales from the Motivated Strategies for Learning Questionnaire positively predicted the number of notes created. In addition, mastery and performance goals positively predicted task value, and work-avoidance goals negatively predicted effort regulation and task value.